Analysis of Activity Program Planning: : A Study Case in Higher Education Institutions - Kafrina, Kafrina (Adpebi International Journal of Multidisciplinary Sciences, 2023)
This study aims to analyze the implementation of activity program planning at the Bureau of General Administration of Planning and Finance (AUPK) Sultan Syarif Kasim Riau State Islamic University and to find out what are the obstacles encountered in implementing the activity planning. This study used a qualitative descriptive method with 14 informants. The results of the study show that in carrying out program planning activities at the AUPK Bureau of UIN Suska Riau when viewed from the point of view of 1). Determining the goals of the planners of activities has a tendency to be misinterpreted or misperceived 2). Formulating the current situation has not been carried out properly where there are several activities that are not in accordance with the strategic plan. (3). Identifying the conveniences and obstacles so far has succeeded in gathering some of the strengths and weaknesses. 4) Develop a series of activities The AUPK Bureau of UIN Suska Riau has made every effort to direct each faculty to be able to select and develop a series of activities to be carried out for 1 fiscal year